A Case of Folding Pattern in Flexible Tripodal of N‐Substituted Bisethylenamine Bridged Pyridazinone Dimers. Issue 4 (3rd February 2017) - Kumar, Ranjeet; Gaurav, Archana; Pal, Shiv; Tewari, Ashish Kumar
Abstract: Present manuscript reports three tripodal molecules for their special structural and conformational properties. Interestingly, X‐ray structure revealed that all these molecules adopt folded conformation in solid state. Further, these molecules are flexible due to linker, may exist in various conformations, the studies have been carried out with different conformers through theoretical calculation in gaseous state. Abstract : The tripodals (2 a‐2 c) have shown the folded conformation in solid state due to extensive intramolecular interactions. These molecules are flexible in nature therefore conformational stabilities have been done with DFT calculations. The DFT calculation revealed that most stable conformation for molecules2 a and2 b are same as crystal conformations while most stable conformation for molecule2 c is different from crystal conformation; however it stable in folded conformation. Overall, all molecules showed folded geometry in solid state and gaseous state.